HUBUNGAN STRES AKADEMIK TERHADAP PROKRASTINASI AKADEMIK DALAM PENGERJAAN SKRISPI PADA MAHASISWA KEPERAWATAN UNIVERSITAS RIAU - Fitri Rabika Zariyati Putri; Arneliwati Arneliwati; Nopriadi Nopriadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Student’s academic stress in working on their thesis has something to do with their behavior, which is academic procrastination. The pupose of this study was to determine the correlations between academic stress and academic procrastination in the research work for Nursing studens at the Univeristy of Riau. This study used a descriptive correlation design and a cross-sectional approach. The research sample was 120 respondents based on inclusion criteria using a total sampling technique. The data analysis using simple descriptive presented in the frequency distribution table and bivariate analysis using the chi-square test. The measuring instrument academic stress questionnaire consisting of 15 statements that have been tested for validity with r count 0.459-0.895 > r table (0.444), and the academic procrastination questionnaire consisting of 18 statements that have been tested valid with r count 0.446-0.795 > r table (0.444). Questioner distributed via goggle form. The result of study indicate that the majority of students experience academic stress in the category of being in the process of working pn their research (77,5) and low academic procrastination behavior (51,7). the result of the square test show that there is a correlation between academic stress and the level of student academic procrastination with p value (0,005) < alpha (0,05). Academic procrastination. This research is expected to be a source of information for students to be more enthusiastic in working on their research and be able to complete their thesis well, and also thereby reducing students academic procrastination behavior.Keywords: College Student, Academik procrastination, Akademik Stress, research.